Climate Risk Management in Agricultural Extension Curriculum Validation and Training of Trainers Workshop in Zambia - Grossi, Amanda; Dinku, Tufa; Hansen, Jim; Mutenje, Munyaradzi; Pele, Winnie Kasoma; Makungwe, Mirriam (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change and year-to-year climate variability have resulted in widespread, pervasive impacts to ecosystems and people in Africa, including increases in the intensity of weather extremes such as droughts and floods. While these shifting and varying temperature and precipitation patterns have affected the productivity of many climate-sensitive sectors, the agricultural sector has been the most impacted, resulting in reduced food availability and increased food prices, ultimately jeopardising food security, nutrition, and livelihoods of millions of people.